2015
DOI: 10.2527/jas.2015-9548
|View full text |Cite
|
Sign up to set email alerts
|

The direct-maternal genetic correlation has little impact on genetic evaluations

Abstract: Obtaining unbiased estimates of the direct-maternal genetic correlation proves far from straightforward for several reasons. Consequently, the use of such over- or underestimated correlations may introduce errors in genetic evaluation models. The objective of our study was to evaluate how the value of the direct-maternal genetic correlation affects EBV. Direct, maternal, and total breeding values were predicted for the ADG or weight at weaning for 3 different species (sheep, rabbits, and pigs) using models tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0
4

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 33 publications
5
20
0
4
Order By: Relevance
“…AGD at birth was correlated with birth weight, whereas AGD at weaning in females was not correlated with weaning weight in the genetic models: in fact, in the first generation, there was a significant negative phenotypic correlation between these. This lack of a consistent relationship between AGD and body weight is important as it means that the body weight cannot be used as a surrogate for AGD, as done by David et al (2015).…”
Section: Discussionmentioning
confidence: 99%
“…AGD at birth was correlated with birth weight, whereas AGD at weaning in females was not correlated with weaning weight in the genetic models: in fact, in the first generation, there was a significant negative phenotypic correlation between these. This lack of a consistent relationship between AGD and body weight is important as it means that the body weight cannot be used as a surrogate for AGD, as done by David et al (2015).…”
Section: Discussionmentioning
confidence: 99%
“…Las r dm a partir del ANAU fueron sobre estimadas en ambos extremos, de +1±0.15 en P30 a -1±0.18 en PD; las r dm negativas y cercanas a la unidad, implica un antagonismo entre los genes para crecimiento y los genes para efectos maternos, y no permite avanzar en el mejoramiento con base en la selección de estos caracteres (María et al, 1993;Matika et al, 2003); por otro lado, estimaciones positivas y cercanas a la unidad, indica que desde el punto de vista genético son la misma característica (Safari et al, 2005). Resultados para r dm negativos y cercanos a la unidad, fueron publicados por Fadili et al (2000) y Neser et al (2000; algunos autores (Robinson, 1996;Lee, 2002) han argumentado las razones porque estos valores pueden ser extremos, y otros cuestionan dichos valores con base en: a) la estructura de los datos no permite separar ambos efectos en el análisis (Clement et al, 2001;David et al, 2015); b) diferencias temporales en los ambientes cuando se expresan los efectos directos y los maternos (Kirkpatrick y Lande, 1989;Bijma, 2006); y, c) reducción en las varianzas de éstos efectos, debida a la selección realizada (Verrier et al, 1994;Lee, 2002).…”
Section: Resultados Y Discusiónunclassified
“…En los modelos para analizar el peso al destete generalmente se incluyen los efectos genéticos directos y maternos, y la correlación genética entre ambos efectos (Willham, 1972;Bijma, 2006); con estimaciones negativas e intermedias (Boujenane y Kansari, 2002;Maniatis y Pollott, 2003), positivas (Abbasi et al, 2012) o nulas (Duguma et al, 2002). Sin embargo, cuando la correlación genética es negativa y cercana a la unidad, expresa un antagonismo entre ambos efectos, con posibles repercusiones en la selección con base en valores genéticos o de cría (Kariuki et al, 2010;Zishiri et al, 2014;David et al, 2015).…”
Section: Materiales Y Métodosunclassified
“…The negative genetic correlation between direct and maternal effects indicates the existence of an antagonism between the two effects for all traits, however, it was shown that its value has a negligible effect on genetic evaluation of individuals (David et al, 2015). In a study that aims to examine the effect of data structure on genetic (co)variance components of early growth in sheep, Maniatis and Pollott (2003) showed that an increase in the number of progeny per dam as well as the proportion of dams with recorded performance have a significant effect on r dm .…”
Section: Discussionmentioning
confidence: 99%
“…An offspring's genotype is composed of inherited genes from sire and dam with equal contribution from both sides. In mammalian species of livestock, dam's ability to provide an environment for its offspring to grow, survive and adaptation in terms of nourishment has a significant impact on offspring's phenotype (Mrode, 2014;David et al, 2015). This is more apparent in sheep as the litter size varies greatly among individuals and a suckling period is crucial (Bradford, 1972).…”
Section: Introductionmentioning
confidence: 99%